Integration of multicultural society: Islamic perspective - Hamisan@Khair, N.S.; Ahmad, M.; Zainan Nazri, M.K.N.; Mohd Nor, M.R.; Mohd Khambali @ Hambali, K. (2012)
Integration of society becomes an important agenda in conveying the message of unity and peace for humankind. For Muslims, this message has been practiced since the time of Prophet Muhammad. This study illustrates how the Prophet had emphasized the importance of integration with Muslims and nonMuslims society in various aspects of their life. This will focuses on the concept of integration of society by exploring the methodology of the Prophet in managing plural society without neglecting the foreign perspective on the subject.